Determinan Kepuasan Konsumen Unit Usaha Dharma Wanita Persatuan UIN Syarif Hidayatullah Jakarta - Zuwesty Eka Putri (Akuntabilitas, 2018)
Dharmawanita UIN Syarif Hidayatullah Jakarta is an activity forum that aims to develop the creativity, expertise of female employees and the wife of an employee of the Syarif Hidayatullah UIN Jakarta. Some activities managed by Dharmawanita are business units engaged in food and beverage providers in the canteen and catering to the academic community of UIN Syarif Hidayatullah in particular and the community in general. The purpose of this study was to obtain empirical evidence related to factors that influence customer satisfaction or customers who use products of the Dharmawanita business unit of UIN Syarif Hidayatullah Jakarta. In addition, this study also aims to analyze the factors that determine consumer purchasing decisions. The results showed that the factors that influence the level of customer satisfaction are: physical appearance, service, menu, taste, and price. Then, factors that influence consumer purchasing decisions whether inside or outside the campus environment are: menu, taste, and price.